Doświadczenia edukacyjne uczniów z niepełnosprawnością ruchową w codzienności szkolnej. Perspektywa biograficzna - Szczesiul, Aleksandra (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The presented text relates to individual experiences of students with motor disabilities in the environment of the school, at different stages of education. The study of everyday school life was carried out in a quality strategy based on the biographical narratives of students. The area of the analysis was focused on uncovering explicit and implicit cultural school patterns, in reference to the individual educational paths of respondents. The image of the school presented in the biographical narratives of pupils is different from the idea of a school for everyone and the official school statements. The surveyed students have objected to the organizational area, work of teachers, relationships with peers. Our study clearly indicates the need for a careful analysis of opportunities and threats of the capacity to implement the project of school for all.
Keywords: educational experiences; educational paths; explicit culture; implicit culture; motor disability; students